2022
DOI: 10.1101/2022.01.11.475801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of larval diet on the life-history traits and phenotypic expression of pyrethroid resistance in the major malaria vectorAnopheles gambiae s.s.

Abstract: The success achieved in reducing malaria transmission by vector control is threatened by insecticide resistance. To strengthen the current vector control programmes, the non-genetic factors underlying the emergence of insecticide resistance in Anopheles vectors and its widespread need to be explored. This study aimed to assess the effects of larval diet on some life-history traits and pyrethroid-insecticide susceptibility of Anopheles gambiae s.s. Three (3) An. gambiae strains, namely Kisumu (insecticid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…After oviposition, eggs typically hatch within 48 hours into motile larvae that cycle through four life-stages called instar (L1-L4), and then transform into nonfeeding pupae within which an adult mosquito develops and emerges from. Differences in egg hatching time and larval development directly influence mosquito body size, vectorial capacity and overall fitness [5][6][7][8][9][10]. The main factors determining these parameters are environmental conditions such as temperature and nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…After oviposition, eggs typically hatch within 48 hours into motile larvae that cycle through four life-stages called instar (L1-L4), and then transform into nonfeeding pupae within which an adult mosquito develops and emerges from. Differences in egg hatching time and larval development directly influence mosquito body size, vectorial capacity and overall fitness [5][6][7][8][9][10]. The main factors determining these parameters are environmental conditions such as temperature and nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…17 ). Other studies have showed that larval nutrition 20,23,24,25 , adult bloodfeeding 26,27 , parasite infection 28,29,30 , environmental temperature 24,31 , or larval exposure to herbicides and/or metal pollutants 32,33 also can modify adult susceptibility to insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…17 ). Other studies have also shown that larval nutrition 20,[23][24][25] , adult blood-feeding 26,27 , parasite infection [28][29][30] , environmental temperature 24,31 , or larval exposure to herbicides and/or metal pollutants 32,33 can modify adult susceptibility to insecticides.…”
mentioning
confidence: 99%